Importance of Anushastra Karma in Urdhwajatrugata Vikara (Shalakya Tantra)- A Conceptual Review (AYUSHDHARA, 2025)
Acharya Sushruta and Vagbhatta mentioned Anushastras in Sutrasthana. Acharya Sushruta has included 14 types of Anushastra. Aims and Objectives: To study Anushastra Prayoga in Urdhwajatrugata Vikara (Shalakya Tantra) mentioned in different classical texts and detail description of Trividha Anushastra Karma. Materials and Methods: This is a conceptual type of study. Textual materials (Bhrihattrayi & various other Samhitas) are used to gather all the available information regarding these Anushastra Prayoga in Urdhwajatrugata Vikara (Shalakya Tantra). Conclusion: The two powerful and less invasive parasurgical techniques, Kshara and Agni Karma, have many uses, particularly in the treatment of pain, which is crucial for preventing recurrence and unintended growth in the various illnesses described in Shalakya Tantra. Jalaukavacharana is also a minimum invasive parasurgical technique which is useful to treat many diseases related to vitiated Rakta Dosha described in Shalakya Tantra.